2011
DOI: 10.1108/02635571111118242
|View full text |Cite
|
Sign up to set email alerts
|

Warehousing in Northern Europe: longitudinal survey findings

Abstract: PurposeThe purpose of this paper is to shed light on the development and change in priority of international warehouse location criteria during a business cycle (i.e. from years 2006 to 2010), by examining the responses of Finnish and Swedish companies on their European‐based facilities. The authors also investigate how the size of European warehouses will develop within medium term.Design/methodology/approachThe authors' research is based on three online surveys completed during years 2006, 2009, and 2010. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Survey research is another of the main methods used to conduct empirical studies. An example is given by Hilmola and Lorentz (2011), who identified three criteria (i.e. distribution costs, road transportation connections, and proximity of manufacturing units) used to determine the warehouse location, and observed that the size of warehouses increased gradually over the years based on a longitudinal survey investigation between 2006 and 2010.…”
Section: Empirical Research Papersmentioning
confidence: 99%
“…Survey research is another of the main methods used to conduct empirical studies. An example is given by Hilmola and Lorentz (2011), who identified three criteria (i.e. distribution costs, road transportation connections, and proximity of manufacturing units) used to determine the warehouse location, and observed that the size of warehouses increased gradually over the years based on a longitudinal survey investigation between 2006 and 2010.…”
Section: Empirical Research Papersmentioning
confidence: 99%
“…For example, certain VALS customisation roles when it comes to the European economies must be undertaken closer to real markets since market fragmentation renders source-based prohibitive for many ranges of goods (Rodrigue & Notteboom, 2010). (Hilmola & Lorentz, 2011), advances that performance of value added services properly, and with better infrastructural ability, improved market accessibility, or presence of desirable labour force could eventually enhance the success, improve and reduce the transaction cost of SC. Also, there is the ability of ensuring product safety, where the proper location for value added services promises commodity safety along the shipment process.…”
Section: Value Added Logistics and Organisation Performancementioning
confidence: 99%
“…Studies related to DSD can relate to quantitative as well as qualitative research. Quantitative research can be found using multicriteria analysis (Ashayeri and Rongen 1997;Önden, Acar, and Eldemir 2016), multicriteria decision-making (Agrebi, Abed, and Omri 2017;Onstein et al 2019b), statistical analysis (McKinnon 1984;Hilmola and Lorentz 2011), factor analysis (Song and Sun 2017), discrete choice analysis (Nozick and Turnquist 2001;Verhetsel et al 2015), spatial modelling (Heitz and Beziat 2016;Klauenberg, Elsner, and Knischewski 2016) and other quantitative models (e.g. Cooper 1984;Ashayeri and Rongen 1997;Olhager, Pashaei, and Sternberg 2015).…”
Section: Literature Reviewmentioning
confidence: 99%